18F-FDG PET-CT Scans in Oncology Patients Treated with Hyaluronic Acid Filler: Not Always a Pitfall - Ilaria Proietti; Chiara Battilotti; Francesca Svara; Ersilia Tolino; Nicoletta Bernardini; Nevena Skroza; Luca Filippi; Concetta Potenza (Case Reports in Oncological Medicine)
The use of hyaluronic acid (HA) fillers in oncology patients undergoing PET-CT scans is a topic of debate due to potential interference with imaging accuracy. A 54-year-old female, postmelanoma metastasectomy in the parotid region with subsequent facial nerve palsy (FNP), received HA filler injections for facial symmetry and functional restoration. Follow-up PET-CT scans showed no interference or artifacts attributable to HA injection, allowing for accurate imaging results. This case suggests that HA fillers administered in oncology patients may not universally pose challenges or disrupt PET-CT imaging interpretation. Due to the possible false positives induced by fillers, the inclusion of aesthetic treatments in patients’ anamnesis is a crucial step to accurately interpret PET-CT images. Although maintaining high level of caution in interpreting PET-CT results after filler injection is essential, our case emphasizes the safety of this procedure in oncology patients undergoing follow-up PET-CT scans.